2005
DOI: 10.1007/s11103-005-0699-3
|View full text |Cite
|
Sign up to set email alerts
|

High heterogeneity within the ribosomal proteins of the Arabidopsis thaliana 80S ribosome

Abstract: Proteomic studies have addressed the composition of plant chloroplast ribosomes and 70S ribosomes from the unicellular organism Chlamydomonas reinhardtii, but comprehensive characterization of cytoplasmic 80S ribosomes from higher plants has been lacking. We have used two-dimensional gel electrophoresis (2-DE) and mass spectrometry (MS) to analyse the cytoplasmic 80S ribosomes from the model flowering plant Arabidopsis thaliana. Of the 80 ribosomal protein families predicted to comprise the cytoplasmic 80S rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
151
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(156 citation statements)
references
References 70 publications
(72 reference statements)
4
151
0
Order By: Relevance
“…We conclude that the RPL10B protein has a specific and essential participation during plant growth, which cannot be replaced by the other RPL10 proteins. Moreover, the presence of the RPL10B isoform has not yet been confirmed in the Arabidopsis 80S ribosome, as no specific tryptic peptide from this protein has been identified by MS/MS in survey experiments (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). Alternatively, it cannot be ruled out that RPL10B has extraribosomal functions during development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We conclude that the RPL10B protein has a specific and essential participation during plant growth, which cannot be replaced by the other RPL10 proteins. Moreover, the presence of the RPL10B isoform has not yet been confirmed in the Arabidopsis 80S ribosome, as no specific tryptic peptide from this protein has been identified by MS/MS in survey experiments (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). Alternatively, it cannot be ruled out that RPL10B has extraribosomal functions during development.…”
Section: Discussionmentioning
confidence: 98%
“…Identification of proteins from purified ribosomes by two-dimensional (2D) electrophoretic analyses followed by mass spectrometry (MS) demonstrated the presence of 79 families of ribosomal proteins in the 80S ribosome. Nearly half are represented by two or more protein spots on 2D gels, indicating that proteins are posttranslationally modified and/or present as different isoforms (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). It is hypothesized that this ribosomal heterogeneity fosters selective translation of specific mRNA under particular cell conditions (Barakat et al, 2001;Szick-Miranda and Bailey-Serres, 2001;Giavalisco et al, 2005;Carroll et al, 2008).…”
mentioning
confidence: 99%
“…In Arabidopsis (Arabidopsis thaliana), ribosomal protein genes exist as families composed of two to seven members that could be differentially incorporated into the cytosolic ribosome under specific situations (Schmid et al, 2005;Byrne, 2009). In this way, ribosomal heterogeneity would allow selective translation of specific mRNAs under particular cell conditions (Barakat et al, 2001;Szick-Miranda and BaileySerres, 2001;Giavalisco et al, 2005;Carroll et al, 2008;Carroll, 2013). Arabidopsis mutants in ribosomal proteins exhibit a large range of developmental phenotypes with extreme abnormalities, including embryonic lethality, suggesting that ribosomes also have specific functions regulating the expression of developmental genes (Van Lijsebettens et al, 1994;Degenhardt and Bonham-Smith, 2008;Byrne, 2009;Horiguchi et al, 2011Horiguchi et al, , 2012Szakonyi and Byrne, 2011).…”
mentioning
confidence: 99%
“…The structure and function of both prokaryotic and eukaryotic ribosomes have been investigated with the prokaryotic emphasis on the ribosomes of Escherichia coli and the eukaryotic emphasis on ribosomes of Baker's yeast (Saccharomyces cerevisiae) and rat (Rattus rattus and Rattus norvegicus). Three-dimensional visualization from crystallographic data have added significantly to the knowledge of eukarytoic ribosome structure (Verschoor et al 1996;Spahn et al 2001Spahn et al , 2004Manuell et al 2005;Chandramouli et al 2008), whereas proteomic analyses have contributed to the knowledge of eukaryotic ribosomal protein (r-protein) composition and posttranslational modifications (Louie et al 1996;Lee et al 2002;Odintsova et al 2003;Chang et al 2005;Giavalisco et al 2005;Manuell et al 2005;Yu et al 2005;Carroll et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies indicated that plant cytosolic ribosomes were slightly smaller than their mammalian counterparts (Cammarano et al 1972;Verschoor et al 1996); however, recent advances in genomics and proteomics have allowed for a more detailed understanding of higher plant ribosomes specifically those of Arabidopsis thaliana (Barakat et al 2001;Chang et al 2005;Giavalisco et al 2005;Carroll et al 2008). Notably, combined proteomic analyses are indicative of ribosome heterogeneity due to expression of specific genes as well as posttranslational modifications.…”
Section: Introductionmentioning
confidence: 99%